The palace of illusions - Miller, Rowenna (Redhook, 2025)
"In the run up to the 1900s World's Fair Paris is abuzz with creative energy and innovation. Audiences are spellbound by the Lumière brothers' moving pictures and Loie Fuller's serpentine dance fusing art and technology. But for Clara Ironwood, a talented and pragmatic clockworker, nothing compares to the magic of her godfather's mechanical creations, and she'd rather spend her days working on the Palace of Illusions, an intricate hall of mirrors that is one of the centerpieces of the world's fair. When her godfather sends Clara a hideous nutcracker for Christmas, she is puzzled until she finds a hidden compartment that unlocks a mirror-world Paris where the Seine is musical, fountains spout lemonade, and mechanical ballerinas move with human grace. The magic of her godfather's toys was real. As Clara explores this other Paris and begins to imbue her own creations with its magic, she soon discovers a darker side to innovation. Suspicious men begin to approach her outside of work, and she could swear a shadow is following her. There's no ignoring the danger she's in, but Clara doesn't know whom to trust. The magic of the two Parises are colliding and Clara must find the strength within herself to save them both."--Provided by publisher.